Multiview three-dimensional reconstruction by millimetre-wave portable camera - Jaime Laviada (Nature Portfolio, 2017)
Abstract Millimetre-wave imaging is a powerful non-destructive inspection technique which has become widely used in areas such as through-the-wall imaging or concealed weapon detection. Nevertheless, current systems are usually limited to either a single view point providing a limited 3D millimeter-wave model or a multiview relying on the accurate movement of a robot arm through precise positions resulting in very bulky systems. In this paper, we present a set of techniques to achieve a multiview millimetre-wave scanner. The aperture of the scanner is kept below 16 cm so it can be portable and, consequently, multiview can be achieved by simple hand movements. In addition, optical images are also acquired with a two-fold purpose: i) building a complementary 3D-model by employing Structure from Movement (SfM) techniques; ii) estimating the scanner position and poses. The proposed technology is illustrated for people screening, proving the capacity of the system to detect hidden weapons.